New Perspectives on Results-Based Blended Finance for Cities - World Bank Group (World Bank, Washington, DC, 2019)
There is clear evidence on the need for cities to rapidly scale-up their investments in climate change mitigation programs and build strong foundations for climate-resilient communities. Investing in low carbon infrastructure and climate resilience can generate competitive returns and is crucial for preventing a reversal of the development gains made in low-income countries up until now. Overcoming the barriers in financing climate-smart infrastructure in cities means adjusting their currently unattractive and inadequate risk-return investment profile. Our analysis explains that well-targeted concessional funding can derisk the financing structure of a project and turn a typical non-bankable project to financial viable one. Additionally, it makes the case for results-based blended finance approaches that strengthen the accountability in project development by linking financing to the achievement of measurable, pre-agreed results. Addressing the lack of creditworthiness, the limited accountability and capacity in institutions and service delivery practices should be at the center of urban investment strategies. The report highlights the need for technical assistance and capacity building programs that will support cities bring order to their financing and accounting practices, support shadow credit ratings and help them become creditworthy. It is estimated that only 20 percent of the 500 largest cities in developing countries are considered creditworthy. Cities and development partners face a common challenge: Making the most effective use of available public finance instruments and disburse scarce public (concessional) funds in a way that maximally leverages private sector co-investments.